Analisis Kinerja Keuangan Pemerintah Daerah Kabupaten Banyuwangi Tahun Anggaran 2018-2020 - Hilda Rizqi Amalia; Berlina Yudha Pratiwi (Politeknik Negeri Jember, 2022)
This study aims to analyze the financial performance of the Banyuwangi Regency Government in 2018 to 2020 using financial ratio analysis. This research design uses descriptive qualitative. The population and samples taken are the 2018-2020 Banyuwangi Regional Government Financial Reports. Data were obtained by means of documentation, and literature study. The results show that the financial performance of the Banyuwangi Regency Government in the ratio analysis of the degree of decentralization in 2018-2020 shows less. In the analysis of the ratio of regional financial dependence in 2018-2020 is very high. In the analysis of the ratio of regional financial independence in 2018-2020 it is very low. In the analysis of the effectiveness ratio of regional original income (PAD) the average 2018-2020 shows less effective. In the 2018–2020 PAD efficiency analysis, it is very efficient. In the analysis of the compatibility ratio for 2018–2020, it shows that the amount of funds owned for operating expenses is 78.84% while operating expenses is 20.06%. The analysis of the growth ratio in 2018-2020 is fluctuating. Penelitian ini bertujuan untuk menganalisis kinerja keuangan Pemerintah Daerah Kabupaten Banyuwangi pada tahun 2018 sampai 2020 dengan menggunakan analisis rasio keuangan. Rancangan penelitian ini menggunakan deskriptif kualitatif. Populasi dan sampel yang diambil adalah Laporan Keuangan Pemerintah Daerah Kabupaten banyuwangi 2018-2020. Data diperoleh dengan cara dokumentasi, dan studi pustaka. Hasil penelitian menunjukkan bahwa kinerja keuangan Pemerintah Daerah Kabupaten Banyuwangi pada analisis rasio derajat desentralisasi tahun 2018–2020 menunjukkan kurang. Pada analisis rasio ketergantungan keuangan daerah tahun 2018 – 2020 sangat tinggi. Pada analisis rasio kemandirian keuangan daerah tahun 2018–2020 rendah sekali. Pada analisis rasio efektivitas pendapatan asli daerah (PAD) rata-rata tahun 2018-2020 menunjukkan kurang efektif. Pada analisis efisiensi PAD tahun 2018–2020 sangat efisien. Pada analisis rasio keserasian tahun 2018–2020 menunjukkan bahwa besar dana yang dimiliki untuk belanja operasi sebesar 78,84% sedangkan belanja operasi 20,06%. Analisis rasio pertumbuhan tahun 2018–2020 bersifat fluktuatif.